A SCI Analysis Model: Research on Influencing Factors of Local E-Government Responsiveness in China - Shaoqing Tian; Rongrong He; Chongli Huang; Qiong Feng; Fan Jiang (Discrete Dynamics in Nature and Society)
In order to explore the influencing factors of the e-government responsiveness in China, the System-Competition-Interaction analysis model was proposed to reflect the ability of e-government to respond to citizens’ demands. 960 pieces of information were collected from 480 local e-government websites in China, and field experiments were conducted on how local governments responded to citizens’ demands. The results show that there are regional differences in e-government responsiveness in China. The response probability of Northeast China is the lowest, and that of western region is the slowest. The response system and neighborhood effect are the core elements that affect e-government responsiveness. The interaction demands of citizens can not significantly affect government responsiveness. According to the research results, the practical enlightenment is that the future should change from “system-driven response” and “competition-driven response” to “citizen-driven response,” which is of a certain practical significance for improving the response level of e-government of local governments in China.